OPINI AUDIT, AUDIT REPORT LAG, REPORTING DELAY, KAP, DAN EPS SEBAGAI DETERMINAN HARGA SAHAM - Rindika, Santika Maya; Setyaningsih, Nina Dwi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The information about company’s financial performance can be obtained by investor in company’s financial report. Some of the informations are audit opinion, audit report lag, reporting delay, KAP, and EPS. That informations are used by investor to do an investment analysis through financial report that can influence investment decision. Investor’s investment decision can influence stock price change. The purposes of this research are to determine the simultan and partial effect of audit opinion, audit report lag, reporting delay, KAP, and EPS on stock price. Research type that is used quantitative method and descriptive approach. Research data are financial reports and stock prices with banking companies listed on Indonesia Stock Exchange (BEI) within year of 2016-2018 as a population. Purposive sampling is used as a sampling method so obtained 23 samples. The research method is using multiple linier regression analysis. The results of this research are simultaneously audit opinion, audit report lag, reporting delay, KAP, and EPS have significant influence to stock prices. Partially, reporting delay and EPS have significant positive influence to stock prices. Meanwhile, audit opinion, audit report lag, and KAP have no effect on stock prices.